METODE DAKWAH KYAI ABDUL GHOFUR PADA MASYARAKAT DUSUN BULUSAN, DESA BULU, KECAMATAN SEMEN, KABUPATEN KEDIRI - Umi Hanik Karimatunnisa; Ropingi; Zuhri Humaidi (Jurnal Mediakita : Jurnal Komunikasi dan Penyiaran Islam, 2018)
The method of da’wah is one of the da’wah elements that should be considered by each dai. There are three da’wah methods in the Qur’an, namely the method of da’wah al-h}ikmah, al-mau’iz}ahal-h} asanah, and al-muja>dalah that must be applied simultaneously through various forms of da’wah. The management of the da’wah method has a major effect because it is also a determining factor in the success of da’wah. Kyai Abdul Ghofur is one of the dai who aplies the whole method of da’wah in the form of bil-lisa>n and bil-h}a>l da’wah according to the Nahdlatul Ulama tradition. His ability to analyze and manage the method of da’wah is very interesting to be studied because he is able to build a new logic in the middle of the community. This study aims to describe the method of da’wah carried out by Kyai Abdul Ghofur and describe the factors that influence the activities of the Kyai Abdul Ghofur’s da’wah to the people in Bulusan Hamlet, Bulu Village, Semen District, Kediri Regency. This study uses a qualitative approach by using three methods of the data collection: observation, interviews, and documentation. The researchers participate and follow actively in the da’wah activities of Kyai Abdul Ghofur. The informant in this study amounted to 21 people who were chosen based on their role and knowledge of the da’wah activities of Kyai Abdul Ghofur. The results of this qualitative study revealed that Kyai Abdul Ghofur applied the method of da’wah al-h}ikmah, al-mau’iz}ahal-h}asanah, and al-muja>dalah in the form of bil-lisa>n and bil-h}a>l da’wah, including: building the religious facilities and religious education; building the Islamic culture; provide solutions to the problems of society with kind words and strong arguments based on the Qur’an and Hadith; delivering the message of da’wah through words that are wise and easy to understand; and applying the variant of preaching to the community with different characteristics. the character and personality of Kyai Abdul Ghofur, the condition of the people who needs messages of da’wah and the message of da’wah that is easily understood are the factors that influence his da’wah activities.